Vida Saludable: Etiquetas de Suplementos Dietéticos Búsqueda por Palabras - Karla P. Shelnutt (EDIS)
FCS8854-Span, a 1-page handout by Karla P. Shelnutt, is the Spanish-language version of FCS-8854, Healthy Living: Dietary Supplement Labels Word Search. It includes words that may be found on dietary supplements labels in a word search format. Published by the UF Department of Family Youth and Community Sciences, June 2008.